Strategic management analysis to improve bed occupancy rate efficiency at PT Alametric Teknologi Asia’s partner hospital - Septiani Aulya Putri; Harries Madiistriyatno; Aswin Naldi Sahim (Privietlab, 2026)
The efficiency of inpatient services serves as a critical indicator for the operational sustainability of a hospital, typically quantified through the Bed Occupancy Rate (BOR). This study aims to evaluate the implementation of strategic management to enhance BOR efficiency at PT Alametric Teknologi Asia’s Partner Hospital. A mixed-methods research design was employed, integrating qualitative and quantitative descriptive approaches. Data collection was conducted through in-depth interviews, field observations, Focus Group Discussions (FGD), and comprehensive document reviews. The analytical framework utilized several strategic management tools, including MCUA, Fishbone Diagram, SWOT analysis, IFE-EFE Matrix, TOWS, and the Quantitative Strategic Planning Matrix (QSPM). The findings indicate that the BOR at PT Alametric Teknologi Asia’s Partner Hospital has not yet aligned with national efficiency benchmarks. Primary operational bottlenecks identified include sluggish registration procedures, suboptimal hospital information systems (SIMRS), and limited referral network collaborations. Consequently, the Weakness–Opportunity (W–O) strategy was designated as the primary turnaround approach. This strategy focuses on digitalizing the registration process, integrating management information systems, and strengthening external partnerships. The execution of these strategic initiatives is anticipated to optimize bed utilization, streamline patient service workflows, and improve overall patient satisfaction and long-term institutional viability.